IMPROVING NUMERACY LITERACY WITH PROBLEM-BASED LEARNING INTEGRATED IN AUGMENTED REALITY MEDIA - Hafizha Arwa Dewanti; Wardhani Utami Dewi (EMTEKA: Jurnal Pendidikan Matematika, 2026)
The numeracy literacy ability of students in Indonesia is still relatively low, which is reflected in the results of PISA and the Minimum Competency Assessment (AKM) which show that many students are able to solve procedural problems, but have difficulties when facing contextual problems that require data interpretation and mathematical reasoning. This study aims to analyze the improvement of students' numeracy literacy skills through the application of the Problem Based Learning (PBL) model integrated in Augmented Reality (AR) media. The study used a quantitative approach with a one-group pretest–posttest design. The subjects of the study were 29 students of grade VIII Ar-Rasyid SMP Muhammadiyah Ahmad Dahlan Metro who were selected using purposive sampling technique. Data were collected through a numeracy literacy test in the form of essay questions given before and after treatment, then analyzed using the Shapiro–Wilk normality test and the Wilcoxon test with the help of SPSS. The results showed that there was a significant improvement in students' numeracy literacy skills, which was shown by an increase in the average score from 18.52 in the pretest to 68.72 in the posttest and the significance value of the Wilcoxon test of 0.000 (<0.05). It can be concluded that PBL learning that is integrated in AR media is effective in improving students' numeracy literacy skills. The implications of this study show that the integration of problem-based learning approaches with AR technology can be an innovative strategy in mathematics learning to support the strengthening of students' numeracy literacy. Kemampuan literasi numerasi siswa di Indonesia masih tergolong rendah, yang tercermin dari hasil PISA dan Asesmen Kompetensi Minimum (AKM) yang menunjukkan bahwa banyak siswa mampu menyelesaikan soal prosedural, tetapi mengalami kesulitan ketika menghadapi masalah kontekstual yang memerlukan interpretasi data dan penalaran matematis. Penelitian ini bertujuan untuk menganalisis peningkatan kemampuan literasi numerasi siswa melalui penerapan model Problem Based Learning (PBL) yang terintegrasi dalam media Augmented Reality (AR). Penelitian menggunakan pendekatan kuantitatif dengan desain one-group pretest–posttest. Subjek penelitian adalah 29 siswa kelas VIII Ar-Rasyid SMP Muhammadiyah Ahmad Dahlan Metro yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui tes literasi numerasi berbentuk soal esai yang diberikan sebelum dan sesudah perlakuan, kemudian dianalisis menggunakan uji normalitas Shapiro–Wilk dan uji Wilcoxon dengan bantuan SPSS. Hasil penelitian menunjukkan bahwa terjadi peningkatan yang signifikan pada kemampuan literasi numerasi siswa, yang ditunjukkan oleh peningkatan skor rata-rata dari 18,52 pada pretest menjadi 68,72 pada posttest serta nilai signifikansi uji Wilcoxon sebesar 0,000 (<0,05). Dengan demikian, dapat disimpulkan bahwa pembelajaran PBL yang terintegrasi dalam media AR efektif dalam meningkatkan kemampuan literasi numerasi siswa. Implikasi penelitian ini menunjukkan bahwa integrasi pendekatan pembelajaran berbasis masalah dengan teknologi AR dapat menjadi strategi inovatif dalam pembelajaran matematika untuk mendukung penguatan literasi numerasi siswa.